Who Should Select New Employees, Headquarters or the Unit Manager? Consequences of Centralizing Hiring at a Retail Chain - Deller, Carolyn; Sandino, Tatiana (The Accounting Review, 2020)
ABSTRACT We examine how changing the allocation of hiring decision rights in a multiunit organization affects employee-firm match quality, contingent on a unit's circumstances. Our research site, a U.S. retail chain, switched from a decentralized hiring model (hiring by business unit managers—in our case, store managers) to centralized hiring (in this study, by the head office). While centralized hiring can ensure that enough resources are invested in hiring people aligned with company values, it can also neglect the unit managers' local knowledge. Using difference-in-differences analyses, we find that the switch is associated with relatively higher employee departure rates and, thus, poorer matches if the business unit manager has a local advantage; that is, if the store serves repeat customers, serves a demographically atypical market, or poses higher information-gathering costs for headquarters. In these cases, the unit manager may be more informed than headquarters about which candidates best match local conditions. Data Availability: The analyses presented in this study are based on data shared by a U.S. retail company. The data are confidential, according to a nondisclosure agreement between the company and the authors.